PENGARUH KELEKATAN DAN KOMUNIKASI DENGAN ORANG TUA TERHADAP KARAKTER REMAJA PERDESAAN - Situmorang, Zervina Rubyn; Hastuti, Dwi; Herawati, Tin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Positive parent-child interaction, that is characterized by positive communication and secured attachment, will affect teenager’s character development. This study aimed to analyze the effect of attachment and communication with parents on teenager’s character development in rural area. A total of 109 teenagers consist of 43 girls and 66 boys were selected using proportional random sampling technique in selected school in study site. Data were collected through self-report techniques by questionnaire. Respondents were asked to fill out questionnaires of the Parent-Adolescent Communication Scale, Adolescent Attachment Questionnaire, and VIA-Youth to measure attachment with parents, communication with parents, and adolescent character. Data were analyzed with descriptive analysis, correlation, and regression. The results showed that the scores of the attachment, communication, and teenager’s characters in rural areas were significantly low. Regression analysis showed that there was no significant effect between teenager’s attachment to parents on all dimensions of adolescent characters. Instead, it was discovered that communication between parent and teenager are positively affected on the dimensions of moral feeling, moral action, and overall characters.